Some features of legal regulation of Operational-Investigative activities in the fight against environmental offenses (Journal of actual problems of jurisprudence, 2018)
This article discusses the issues affecting the problem of environmental safety. And measures for their prevention are proposed.Key words: environmental security, the fight against crime, objectives, environmental offenses, latency, crime, statistics.